2016
DOI: 10.1002/ece3.2534
|View full text |Cite
|
Sign up to set email alerts
|

Flies evolved small bodies and cells at high or fluctuating temperatures

Abstract: Recent theory predicts that the sizes of cells will evolve according to fluctuations in body temperature. Smaller cells speed metabolism during periods of warming but require more energy to maintain and repair. To evaluate this theory, we studied the evolution of cell size in populations of Drosophila melanogaster held at either a constant temperature (16°C or 25°C) or fluctuating temperatures (16 and 25°C). Populations that evolved at fluctuating temperatures or a constant 25°C developed smaller thoraxes, win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
0
22
1
Order By: Relevance
“…Increasing temperature tends to be associated with smaller cell sizes in a variety of organisms (reviewed in [61,62]; also see [63][64][65][66][67][68]). Small cells (and organisms containing them) tend to have higher mass-specific metabolic rates than large cells (and organisms containing them) [26,[69][70][71][72][73][74][75][76][77].…”
Section: Implications Of Results For Theorymentioning
confidence: 99%
“…Increasing temperature tends to be associated with smaller cell sizes in a variety of organisms (reviewed in [61,62]; also see [63][64][65][66][67][68]). Small cells (and organisms containing them) tend to have higher mass-specific metabolic rates than large cells (and organisms containing them) [26,[69][70][71][72][73][74][75][76][77].…”
Section: Implications Of Results For Theorymentioning
confidence: 99%
“…Indeed, other studies on these lines have revealed divergence in other traits including body size, cell size, and metabolism across treatments (Adrian et al. ; Alton et al. ).…”
Section: Discussionmentioning
confidence: 97%
“…It may be that the evolved changes in recombination rate among selection regimes are indirect consequences of natural selection on other phenotypes that are relevant for the experimental evolution treatments. Indeed, other studies on these lines have revealed divergence in other traits including body size, cell size, and metabolism across treatments (Adrian et al 2016;Alton et al 2016).…”
Section: Genetic Variation In Recombinationmentioning
confidence: 99%
“…Smaller cells speed metabolism during periods of warming but require more energy to maintain and repair. At a low temperature, when metabolism proceeds slowly, large cells should provide a sufficient surface to transport the metabolites required to sustain life (Adrian et al 2016). Birds are in relative metabolic rest in winter.…”
Section: Discussionmentioning
confidence: 99%